2021
DOI: 10.1093/brain/awab013
|View full text |Cite
|
Sign up to set email alerts
|

Apathy in small vessel cerebrovascular disease is associated with deficits in effort-based decision making

Abstract: Patients with small vessel cerebrovascular disease frequently suffer from apathy, a debilitating neuropsychiatric syndrome, the underlying mechanisms of which remain to be established. Here we investigated the hypothesis that apathy is associated with disrupted decision making in effort-based decision making, and that these alterations are associated with abnormalities in the white matter network connecting brain regions that underpin such decisions. Eighty-two patients with MRI evidence of small vessel diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 111 publications
3
55
0
Order By: Relevance
“…Here, we confirmed strong relationships between effort discounting, and responses on all three rating scales. This replicates previous studies that have reported a relationship between heightened effort discounting and apathy 28 , 29 , 72 74 . Less work has been done examining the relationship between effort discounting and fatigue, although this is an area of increasing interest 16 , 21 , 31 .…”
Section: Discussionsupporting
confidence: 91%
“…Here, we confirmed strong relationships between effort discounting, and responses on all three rating scales. This replicates previous studies that have reported a relationship between heightened effort discounting and apathy 28 , 29 , 72 74 . Less work has been done examining the relationship between effort discounting and fatigue, although this is an area of increasing interest 16 , 21 , 31 .…”
Section: Discussionsupporting
confidence: 91%
“…Negative symptoms are associated with specific changes within a fronto-striatal network that is closely associated with EBDM (Moran et al, 2019;Shukla et al, 2019;Xu et al, 2019). This is particularly interesting as this network is also associated with clinical apathy in neurological diseases (Hollocks et al, 2015;Saleh et al, 2021). Exploring the neural and behavioural differences between negative symptoms across diseases is an exciting future area of research.…”
Section: Discussionmentioning
confidence: 99%
“…Further, clinical apathy as defined in this manner contains several symptom dimensions (e.g., behavioural, social, and emotional) which overlap with MAP symptoms (Marin et al, 1991;Kirkpatrick et al, 2006;Sockeel et al, 2006;Ang et al, 2017). Behaviourally, apathetic patients with cerebrovascular (Le Heron et al, 2018a;Saleh et al, 2021), and Parkinson's disease (Le Heron et al, 2018b) display reward processing deficits when performing an EBDM task. Specifically, they accept less monetary offers at low reward compared to their motivated counterparts (Le Heron et al, 2018a,b;Saleh et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations